Broad Electrocardiogram Syndromes Spectrum: From Common Emergencies to Particular Electrical Heart Disorders—Part II - Alexandr Ceasovschih; Anastasia Balta; Victorița Șorodoc; Krishnaraj Rathod; Ahmed El Gohary; Serghei Covantsev; Richárd Masszi; Yusuf Ziya Şener; Alexandru Corlăteanu; Syed Haseeb Raza Naqvi; Alexandra Grejdieru; Nicholas G. Kounis; et al. (Diagnostics)
The electrocardiogram (ECG) remains a cornerstone of modern cardiology, providing rapid, non-invasive, and widely accessible diagnostic insights. While ECG interpretation is an essential skill for clinicians, certain patterns can be subtle or atypical, posing diagnostic challenges. In our previous review (doi.org/10.3390/jpm12111754), we explored several uncommon ECG syndromes with significant clinical implications. However, the spectrum of electrocardiographic abnormalities extends far beyond those initially discussed. In this second installment, we expand our discussion of rare and underrecognized ECG syndromes, including Long QT, Jervell and Lange-Nielsen, Romano–Ward, Andersen–Tawil, Timothy, Short QT, and Twiddler’s syndromes, as well as Noonan, Barlow’s, Bundgaard, BRASH, Carvajal, Naxos, and Danon disease. We highlight their clinical context, characteristic findings, and implications for diagnosis and management. These conditions range from acute, life-threatening emergencies requiring immediate intervention to chronic electrical disorders necessitating long-term monitoring and risk stratification. By broadening our focus, we aim to enhance awareness and recognition of these entities, ultimately improving patient outcomes through timely and accurate diagnosis.